Diversity of Mammomonogamus (Nematoda: Syngamidae) in large African herbivores - Červená, Barbora (2018)
Four species of Mammomonogamus are known from large African herbivores. A recent study demonstrated that a single Mammomonogamus species was shared by both western lowland gorillas (Gorilla gorilla gorilla) and African forest elephants (Loxodonta cyclotis) in Central African Republic, suggesting lower species diversity than previously described in literature. We examined more than 500 fecal samples collected from sympatric African forest elephants, western lowland gorillas, and African forest buffaloes (Syncerus caffer nanus) at four study sites across Central Africa and examined them by coproscopic methods to detect Mammomonogamus eggs, which were found at three of the study sites. Subsequently, sequences of 18S rDNA, 28S rDNA, and cox1 amplified from individual eggs were analyzed. Phylogenetic analyses of both nuclear and mitochondrial DNA revealed two clades: one formed by sequences originating from Gabonese buffaloes and the other comprising gorillas and elephants. The gorilla–elephant clade was further differentiated depending on the locality. We show the existence of at least two distinct species of Mammomonogamus, M. loxodontis in elephants and gorillas and M. nasicola in buffaloes. The available information on Mammomonogamus in African herbivores is reviewed.